Social Difference and the Problem of the “Unique Individual”: An Uneasy Legacy of Child-Centred Pedagogy - Norquay, Naomi (Canadian Journal of Education/Revue canadienne de l’éducation, 1999)
In this article I explore how the discourse of child-centred pedagogy both shapes and limits how teachers talk about issues of social difference in their teaching practice. By examining the testimony of four experienced inner-city elementary teachers, I problema- tize two key tenets of child-centred pedagogy: the child as “unique individual” and the teacher as neutral change agent. I also explore these two subject positions in relation to Whiteness and White privilege. What does child-centred pedagogy hold in common with White privilege, in terms of how it constructs social identities? This article is framed by a concern for the ramifications of the legacy of child-centred pedagogy for current-day teacher education students, who are learning to teach in increasingly diverse contexts. Dans cet article, l’auteure explore comment le discours de la pédagogie centrée sur l’enfant façonne et limite à la fois la manière dont les enseignants abordent les questions de différence sociale dans leur enseignement. En examinant le témoignage de quatre enseignants d’expérience travaillant dans des écoles de quartiers défavorisés, l’auteure se penche sur deux principes clés de la pédagogie centrée sur l’enfant : l’enfant comme indi- vidu unique et l’enseignant comme agent neutre de changement. Elle explore la question de privilège liée à l’appartenance à la majorité de race blanche. Cet article tient compte de l’inquiétude que suscitent les ramifications du legs de la pédagogie centrée sur l’enfant sur les étudiants-maîtres d’aujourd’hui qui sont appelés à enseigner dans des contextes de plus en plus diversifiés.